Skills mismatch: employability and entrepreneurial skills of graduates - Pereira, Elisabeth (2016)
The project #EuropeHome (#EH) proposes a scheme with an aim to ensure favourable circumstances for students to earn competences, which are highly valued in the labour market and, thus, increase the employability of prospective graduates. Involving labour market actors in the design and delivery of programmes at universities, and including practical experience in courses will help to attune the curricula to current and emerging labour market needs and foster entrepreneurial awareness. (...)